Importancia de vegetación urbana en la mitigación de la isla de calor en la zona céntrica de la ciudad de Calceta - Vitery Rivas, Jean Pierre Antonio (2022)
This study carried out an analysis of the importance of urban vegetation in the effect of heat islands in the urban area (ICU) of the city of Calceta in the years 2014, 2015, 2016, 2017 and 2019. It was carried out from geographic information systems and multispectral images of the Landsat 8 satellite where the spectrum bands 4,5 and 10 were processed obtaining normalized Differential Vegetation Index (NDVI) and the Terrestrial Surface Temperature (LST) in which the areas that present the higher surface temperatures over the years; in order to make a correlation that allowed us to identify if they affect the ICU effect. The results indicated a minimum NDVI of -0.040 corresponding to the year 2019, in the 5 maps it is shown that the minimum values of -0.040 were found in the central urban area of the City while the maximum values of the 0.631 NDVI were presented in the limits from the rural area. Minimum terrestrial surface temperatures of 17 ºC in 2014 and maximums of 32 ºC in 2016 were presented. The heat island maps presented a slightly similar geometry, located in the center of the map. An inverse and significant correlation was found between LTS and NDVI temperatures associated with the appearance of ICUs, since as the temperature increases, the value of the NDVI decreases, the heat island effect affects the downtown area of the city.